A colonização da macrófita invasora Hydrilla verticillata aumenta com a pressão de propágulos mas não é afetada por competição com uma planta nativa. - Franco, Nayara Louback (2017)
Invasions are a threat to biodiversity because non-native species can lead to several ecologic and economic impacts in invaded ecosystems. Propagule pressure and biotic resistance are mechanisms that influence invasive species success. Hydrilla verticillata is a submerged macrophyte that was introduced worldwide, including the Paraná River basin. We hypothesized that H. verticillata establishment is affected negatively by a native competitor (biotic resistance), but it is positively influenced by propagule pressure. To test our hypothesis we developed a fully cross experiment outdoor, using the native isoetid-like Echinodorus tenellus as competitor, at different levels of propagule pressure. Propagule pressure was effective in increasing H. verticillata colonization while biotic resistance only decreased the development of hydrilla roots, but it was not enough to prevent hydrilla colonization even at the lowest propagule pressure. We conclude that propagule pressure is an important determinant of hydrilla success and that E. tenellus does not prevent hydrilla establishment. The lack of effect of this native macrophyte on H. verticillata success is likely related to the fact that the former species is a typical isoetid like-plant, what makes it to be competitively inferior to eloideids like the latter species.